2016
DOI: 10.1055/s-0042-103495
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Adulterants in Herbal Medicinal Products: A Review

Abstract: Many herbal medicinal products have been found to contain synthetic prescription drugs as chemical adulterants. This has become evident by the number of toxicity cases and adverse reactions reported in which casualties were reported via analytical techniques that detected the presence of chemical adulterants in them, which could be responsible for their toxicity. The adulteration of herbal medicinal products with synthetic drugs continues to be a serious problem for regulatory agencies. This review provides up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 73 publications
0
52
0
Order By: Relevance
“…Finally, adulteration of supplements sold for blood sugar management may be relatively infrequent in the USA and far less than that seen in weight loss, body‐building and sexual performance enhancement products. Several recent reviews have indicated that adulteration of products including those for weight loss, sports, and sexual performance enhancement is far more prevalent than adulteration of supplements sold for blood sugar control . These reviews include data and information from emergency department visits, reviews of cases of toxicity due to chemical adulterants in botanical dietary supplements, and reviews of the classes of drugs frequently seen as being added illegally to specific classes of supplements .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, adulteration of supplements sold for blood sugar management may be relatively infrequent in the USA and far less than that seen in weight loss, body‐building and sexual performance enhancement products. Several recent reviews have indicated that adulteration of products including those for weight loss, sports, and sexual performance enhancement is far more prevalent than adulteration of supplements sold for blood sugar control . These reviews include data and information from emergency department visits, reviews of cases of toxicity due to chemical adulterants in botanical dietary supplements, and reviews of the classes of drugs frequently seen as being added illegally to specific classes of supplements .…”
Section: Resultsmentioning
confidence: 99%
“…(Roh et al, 2011) Methods involving LC coupled with various detectors (usually MS), have the advantage of high sensitivity; however, they also have disadvantages of being laborious, time consuming and the fact that they are too selective and cannot provide global information in detecting a particular component, because compositions of drugs vary among different brands (Monakhova et al, 2012). These methods were also considered to have inadequate reliability for screening because herbal medicines contain a complex mixture of many components which may interfere with chromatographic and mass spectroscopic assays (Calahan et al, 2016). Furthermore, chromatographic methods can yield false-positive results; therefore, these methods cannot be ideal for screening of adulterated drugs in THMs (Vaysse et al, 2010).…”
Section: Quadrupole Time Of Flight Liquid Chromatography Mass Spectromentioning
confidence: 99%
“…Another useful and effortless technique used for herbal components analysis is CE, which is fast, cheap, and needs smaller amount of the samples [95,106]. It is a relatively new analytical technique based on the separation of charged analytes through a small capillary under the impact of an electric field.…”
Section: Cementioning
confidence: 99%
“…As flavonoids are negatively charged, CE is a specifically adapted method to separate these compounds. The coupling between the capillary isotachophoresis and zone capillary electrophoresis was applied for the quantitative determination of flavonoids [95,100,106].…”
Section: Cementioning
confidence: 99%
See 1 more Smart Citation